O valor da política de remuneração: aplicação da análise da utilidade ao caso de uma empresa no Brasil - Moura Netto, Lucio de (2007)
The literature on Human Resources advises its professionals to emphasize the potential contribution that may be made by the projects and programs to the business objectives of their companies, whenever they seek approval for the investments and priority allocation required for their development and implementation. The companies, pressed by the rising competition, expect that their HR professionals justify those investments in a manner that clearly demonstrates the benefits that the programs may bring to the achievement of their business objectives. To do that, they should speak a language that necessarily relates to the financial and economic results of their companies. If the influence ability of HR areas is low, or if the priority given to the implementation of their programs is insufficient, this is nothing more nothing less than a rational response from the part of their companies management, who, despite intuitively “knowing” the benefits of their activities, does not have any objective measure of such benefits. In the absence of such measure, the organization cannot adequately prioritize HR programs into their investment plans. Utility Analysis offers an answer to this problem. It consists of a family of theories and metrics designed to describe, predict and/or explain how useful and desirable are the decision options presented by the various HR programs – selection, training, performance evaluation, compensation, etc., and may be seen as a cost benefit analysis process: costs reduce utility and benefits increase it. Utility Analysis is a tool well suited to the business environment because it insists that both costs and consequences of decisions be always considered beforehand. Its merit resides in that it results in decisions that are based on robust, rational and conscious analysis, and expressed in the language most used in today’s business world – costs, benefits, returns on investments and their effect on the bottom line of financial and economic results. In this study we execute the methodology defined by Sturman et al. (2003), which is aimed at using Utility Analysis to evaluate the economic value of different compensation policies, to the case of a large bank in Brazil. Our conclusions demonstrate the usefulness of Utility Analysis in justifying the adoption of compensation policies that add high value to the business. The justification is based on estimates of the incremental value added by the human resources that such policies help to retain, on one hand, and by the risks involved in their implementation, on the other. Such compensation policies, if judged by the traditional standards of costs, would certainly be discarded. VIII We demonstrate that Utility Analysis provides a common language between the HR area, senior management and other areas of any company – contribution to its business objectives. This should facilitate the communication of benefits, implementation and monitoring of HR programs and initiatives.